Systematic Review of Mind-Body Interventions to Treat Myalgic Encephalomyelitis/Chronic Fatigue Syndrome - Khanpour Ardestani, Samaneh (Medicina (Kaunas), 2021)
Background and Objectives: Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is a chronic condition distinguished by disabling fatigue associated with post-exertional malaise, as well as changes to sleep, autonomic functioning, and cognition. Mind-body interventions (MBIs) utilize the ongoing interaction between the mind and body to improve health and wellbeing. Purpose: To systematically review studies using MBIs for the treatment of ME/CFS symptoms. Materials and Methods: MEDLINE, EMBASE, CINAHL, PsycINFO, and Cochrane CENTRAL were searched (inception to September 2020). Interventional studies on adults diagnosed with ME/CFS, using one of the MBIs in comparison with any placebo, standard of care treatment or waitlist control, and measuring outcomes relevant to the signs and symptoms of ME/CFS and quality of life were assessed for inclusion. Characteristics and findings of the included studies were summarized using a descriptive approach. Results: 12 out of 382 retrieved references were included. Seven studies were randomized controlled trials (RCTs) with one including three reports (1 RCT, 2 single-arms); others were single-arm trials. Interventions included mindfulness-based stress reduction, mindfulness-based cognitive therapy, relaxation, Qigong, cognitive-behavioral stress management, acceptance and commitment therapy and isometric yoga. The outcomes measured most often were fatigue severity, anxiety/depression, and quality of life. Fatigue severity and symptoms of anxiety/depression were improved in nine and eight studies respectively, and three studies found that MBIs improved quality of life. Conclusions: Fatigue severity, anxiety/depression and physical and mental functioning were shown to be improved in patients receiving MBIs. However, small sample sizes, heterogeneous diagnostic criteria, and a high risk of bias may challenge this result. Further research using standardized outcomes would help advance the field.